The Influence of Human Resource Management Audit on Employee Performance with Motivation and Work Environment as Moderating Variables on Employees of Bank BPD DIY Yogyakarta Syariah Branch Office - Pratiwi, Krisnandini Wahyu (AIBPM Publisher, 2022)
This study aims to determine and analyze how the effect of Human Resource Management Audit on employee performance with motivation and work environment as moderating variables. This research was conducted on employees of Bank BPD DIY Yogyakarta Syariah Branch office. Data collection was carried out from August 2022 to September 2022. The data used in this research are primary data and secondary data. The sampling technique in this study used a saturated sample technique with a total of 31 respondents. The data analysis method used in this study is multiple linear regression and MRA Analysis (Moderated Regression Analysis) with the help of the SmartPLS 3.0 application. The results of this study show: 1) Human Resource Management Audit has a positive and significant effect on employee performance at BPD DIY Syariah Bank Yogyakarta. 2) Motivation is unable to moderate the effect of human resource management audits of employee the performance at Bank BPD DIY Syariah Yogyakarta. 3) The work environment is unable to moderate the effect of human resource management audits on performance on employees of Bank BPD DIY Syariah Yogyakarta.